(In) visibility of notifications of violence against children and adolescents registered in a municipality in southern Brazil - Arruda da Silva, Priscila; Lerch Lunardi, Valéria; Dalke Meucci, Rodrigo; Algeri, Simone; Peixoto da Silva, Michele; Pivoto Franciscatto, Flávia (Investigación y Educación en Enfermería, 2019)
Objective. To know the perception of health, education and social service professionals about the records and notifications of violence against children and adolescents, carried out in a municipality in the south of Brazil. Methods. This is an exploratory, descriptive, and qualitative approach, specifically developed in places that integrate children and adolescents victims of violence. Ten professionals participated, including three nurses, one doctor, two social workers, two psychologists, one tutor, and one educator. Data collection was performed through a semi-structured interview. The statements were submitted to discursive textual analysis. Results. The analysis showed that the act of recording and reporting violence against children and adolescents is still not a routine practice for health professionals. The registration and formal communication of the information should be considered as a priority; however, the results showed that the protection of the victim seems to overlap with the registry. The study identified important elements in strategies for coping with violence against children and adolescents: centralization of notifications in a single service; creation of a notification flow; existence of an advisory team to deal with cases of violence; and completion of compulsory notification by education and social assistance professionals. Conclusion. For the professionals, the routine attendance of situations involving violence, but not formalized through the notification form, has contributed to the underreporting and invisibility of the cases. How to cite this article: Silva PA, Lunardi VL, Meucci RD, Algeri S, Silva MP, Franciscatto FP. (In) visibility of notifications of violence against children and adolescents registered in a municipality in southern Brazil. Invest. Educ. Enferm. 2019; 37(2):e11.